Wireless rogowski coil sensor based on partial discharge detection signal for on-line condition monitoring in the medium voltage power cables / \c Mohamad Nur Khairul Hafizi bin Rohani. - Mohamad Nur Khairul Hafizi Rohani (School of Electrical Systems Engineering, Universiti Malaysia Perlis, 2017)
The aim of this research is to design a wireless RC sensor based on PD detection technique for on-line condition monitoring on MV XLPE underground power cables. This project also compares the simulation findings with experimental results, so as to conclude the design accuracy. The main objective of this research can be summarized as follows ; to develop four different shapes RC sensor prototype such as circular, square, rectangular and oval using high strength Acrylonitrile Butadine Styrene (ABS) material for PD detection on MV XLPE underground power cables ; to implement a non-inverting operational amplifier (op-amp) and active Butterworth high-pass filter using Sallen-key topology with lower cut-off frequency 500 kHz ; to integrate the RC sensor prototype with a wireless system using field programmable gate-array (FPGA) to transmit the PD notification signal from measuring site to the server unit. Sigma-Delta analog to digital converter (ADC) topology is used to convert high frequency of analog PD signal to digital signal. Peak detection and threshold technique of PD signal is applied.